Rancang Bangun Sistem Informasi Sekolah Berbasis Web Menggunakan Framework CodeIgniter di SMP Nurul Hikmah - Ahmad Riyadi; Fajar Agung Nugroho (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The design of a web-based school information system using the codeigniter framework at Nurul Hikmah Middle School was created to build a school information system that is expected to facilitate data processing and data search in schools, so that data processing of this school information system can be more accurate, information system design schools are designed using the codeigniter framework programming language and MySQL database which in the final stage can function to facilitate data processing, for the implementation phase using UML (Unified Modeling Language) which can analyze input data and output data. The waterfall method is carried out with a systematic approach, starting from the system requirements stage and then moving on to the analysis, design, coding, testing/verification, and maintenance stages. Step by step that must be completed one by one (cannot jump to the next stage) and run sequentially, therefore it is called a waterfall. To ensure the system runs well, two stages of testing are carried out, namely white box and black box testing in the process of managing student data, managing grades data and managing academic data as well as testing showing the final report on student report card scores.